(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Communications have grown at an exponential rate throughout the modern period. The need of security in contexts with limited resources has been highlighted by applications such as online banking, personal digital assistants, mobile communication, smartcards, etc. With low key sizes and good security on par with other common public key techniques, elliptic curve cryptography (ECC) is an ideal tool for cryptography. ECC is a method of data encryption that relies on keys. Encryption and decryption are the main focusses of ECC, which relies on public and private key pairs. The Elliptic Curve Discrete Logarithm Problem (ECDLP) is a computationally intractable inverse process that gives rise to ECC methods, which are based on scalar multiplication of elliptic curve points. An exhaustive examination of the difficulties in creating ECC-based systems was accompanied by an assessment of current ECC solutions. Domain parameter selection, scalar multiplication, point multiplication, elliptic curve generation, key generation, key size selection, security measures, applications, and so on are some of the difficulties highlighted in the study.